IEEE International Conference on Robotics and Automation, 2004. Proceedings. ICRA '04. 2004 2004
DOI: 10.1109/robot.2004.1308838
|View full text |Cite
|
Sign up to set email alerts
|

Improving teleoperation: reducing mental rotations and translations

Abstract: Abstract-We consider teleoperation in which a slave manipulator, seen in one or more video images, is controlled by moving a master manipulandum. The operator must mentally transform (i.e. rotate, translate, scale, and/or deform) the desired motion of the slave image to determine the required motion at the master. Our goal is to make these mental transformations less taxing in order to decrease operator training time, improve task time/performance, and expand the pool of candidate operators. In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…Prior work has shown that a lack of situation awareness correlates with poor operator performance [5,32], often stemming from the operator's lack of understanding of the remote system's surroundings, status, or location [9]. The use of standard video cameras that are designed to provide only a narrow range of view can lead to what is known as the soda straw or keyhole effect, where the limited visibility requires extra user effort to achieve awareness levels similar to having a direct view of the environment [48].…”
Section: Narrow View Limitationsmentioning
confidence: 99%
“…Prior work has shown that a lack of situation awareness correlates with poor operator performance [5,32], often stemming from the operator's lack of understanding of the remote system's surroundings, status, or location [9]. The use of standard video cameras that are designed to provide only a narrow range of view can lead to what is known as the soda straw or keyhole effect, where the limited visibility requires extra user effort to achieve awareness levels similar to having a direct view of the environment [48].…”
Section: Narrow View Limitationsmentioning
confidence: 99%
“…DeJong, et al [7] investigated optimizing the teleoperator's interface in order to reduce the mental workload by minimizing the number of mental rotations and translations that the teleoperator must do in order to gain situational awareness. They showed that by organizing the interface and displays in an effective way, the transformations required to convert the robot's desired motion -as seen in the operator's view of the world -into a command to the input device can be minimized, reducing training and task times and increasing task performance.…”
Section: Related Workmentioning
confidence: 99%
“…We conjecture that moving the robot in its end-effector coordinates is more difficult and causes delays in perception and spatial processing (DeJong, Colgate, & Peshkin, 2004) of the EE POR frame mapped to the joysticks ,leading to greater time taken in EE kinematics. WR kinematics seemed to reduce recovery time from convoluted orientations, due to its decoupled rotation and translation components, hence shorter times were observed.…”
Section: Discussionmentioning
confidence: 99%